The Influence of Perceived Sustainability, Perceived Authenticity, Perceived Risk, Perceived Value, Perceived Benefit and Perceived Trustworthiness on Attitude Toward Local Product: A Study on Buah Merah Papua as a Local MSME Product in Jayapura City - Indra Eka Wardana Toii; Xenia Irene Sandy Landjang; Lisa Gresti Sella Damanik; Yuni Riskita Mangopo; Rizka Cintya Edwar (Sean Institute, 2026)
The increasing consumer awareness of sustainability, authenticity, and trust in local products has become an important factor in enhancing the competitiveness of local micro, small and medium enterprises (MSMEs) in Indonesia. One of the distinctive local products with significant cultural and economic value is Buah Merah Papua which has gained increasing attention from consumers in regional markets. This study aims to examine the influence of perceived sustainability, perceived authenticity, perceived risk, perceived value, perceived benefit and perceived trustworthiness on consumer’s attitudes toward local products with a focus on Buah Merah Papua as a local MSME product in Jayapura City. This study employed a quantitative research approach using a structured questionnaire as the primary data collection instrument. The data were collected through questionnaire distribution to 264 respondents selected using a purposive sampling technique with criteria based on consumers who had previously purchased or consumed Buah Merah Papua products. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results indicate that perceived authenticity, perceived risk, and perceived trustworthiness have a positive and significant effect on attitude toward local product. Meanwhile, perceived benefit, perceived sustainability, and perceived value were found to have no significant influence on attitude toward local product. These findings highlight the important role of authenticity, trust and risk perception in shaping positive consumer attitudes toward local products. This study contributes to the development of local product marketing literature and provides practical implications for MSME actors in strengthening product positioning, building consumer trust and improving the competitiveness and sustainability of local products in regional and national markets.